Teaching English through Online Games for Junior High School Students - Sastika Seli (Premise: Journal of English Education and Applied Linguistics, 2015)
Teaching language is an attractive activity both for the teacher and for the acceptor. They can interact together in this act. Teaching English is a challenge for the teachers to make the students interest in English because as we know English is not the first language for some countries in this world including Indonesia. There are various ways and ideas to teach English so that it can be fun and interest to be taught and to be learnt. But those ways and ideas also should be an up date method and also use a modern technology to be implemented. Along with the development of modern technology, the teachers should involve with it and make it as a part of English teaching tools. Two of the famous and sophisticated tools are computer and the internet. These things have a close relation to be urgent equipment for people. In this article, the writer wants to purpose the use of online games as a way to teach English for junior high school. Te article aims to give another teaching alternative in attracting the junior high school students to learn English in funny and enjoyable way. Through online games they do not only can play the various games but also indirectly they do the exercises of English skills.